Penerapan Pembelajaran Kontekstual (CTL) dalam Meningkatkan Prestasi Belajar Siswa pada Mata Pelajaran IPA Sains Kelas VI di MIS Al-Yaminy Dompu Tahun Pelajaran 2019/2020 - Runa (Jurnal LENTERA: Jurnal Studi Pendidikan, 2020)
The success of the quality of education depends on various factors, including the students themselves, subject matter, teachers and parents, the learning strategies prepared by the teacher. In teaching, especially in Science, an appropriate learning strategy is needed, such as the CTL learning approach. This study aims to determine how the application of contextual learning (CTL) can improve student achievement in Science and Science subjects Class VI at MIS Al-Yaminy Dompu in the 2019/2020 academic year. The research design used was classroom action design (Classroom Action Research) and in short PTK. From the results of the research, it is proven that it can improve the learning achievement of class VI. In the first cycle, the students' absorption capacity was 57.60% and classically 33.33% (sufficient category). In cycle II, there was an increase in student absorption by 68.60% and classically 73.33% (good category) while in the action cycle III, there was an increase in student absorption by 75.13% and classically 86.67% (good category) from cycle II. The results of the study can be concluded that the application of contextual learning (CTL) is effective in improving student learning achievement in Science Class VI subjects at MIS Al-Yaminy in the 2019/2020 Academic Year